Spontaneous ureterocele wall rupture by a ureteral stone: A case report - Taisuke Ezaki; Hiroshi Hongo (Urology Case Reports, 2023)
Ureterocele, a type of ectopic ureter characterized by cystic dilation of the distal ureter, can sometimes contain stones. Here, we present the case of a 67-year-old woman who was under observation for ureteral stone and experienced spontaneous ureterocele wall ruptured due to the stone. As illustrated in the present case, conservative observation, which is recommended as initial management of stones in ureterocele to reduce the risk of vesicoureteral reflux following transurethral ureterocele incision, may be associated with increased risk of ureterocele wall rupture and subsequent vesicoureteral reflux.